Supporting the implementation of AI in business communication: the role of knowledge management - Iaia, Lea; Nespoli, Chiara; Vicentini, Francesca; Pironti, Marco; Genovino, Cinzia (Journal of knowledge management, 2024)
Purpose Although the use of artificial intelligence (AI) has been estimated to be up to 56% in the last decade, the adoption rate of AI for communication activities is still low. The lack of in-depth literature on the subject, and the limited sharing of the experience gained by companies, limits the creation, dissemination and consolidation of understanding in this area. The purpose of this study is to solve the problem of the absence of knowledge, identification, skills development and introduction of an innovation (such as the AI in the business communication) in the company, with the principles of knowledge management (KM). Design/methodology/approach This study adopts the perspective of KM to provide guidelines for the definition of standards and facilitate the introduction of AI in business communication. Findings To the best of the authors’ knowledge, this study is the first to relate the perspectives of business communication, AI and KM, activating a virtuous circle between KM and AI. At the centre of the proposed model are people, processes and technologies, based on which KM represents the ideal perspective to define the implementation of AI. This is primarily from the perspective of augmented intelligence, owing to the inability of AI to completely replace humans in the business communication processes, as it lacks, among others, emotional intelligence. Research limitations/implications This study finds in KM a possible strategy to solve the problems faced so far in applying AI in business communication processes, providing a model capable of transforming and adapting itself to the context, thanks to the open approach. Originality/value This study contributes to the literature by linking the introduction of emerging technology (AI) in a specific process, such as business communication, from the KM perspective.